Integrating phenotypic analyses and color parameters: a multidimensional framework for precise color characterization in eggplant fruit - Zhang, Yiying; Chen, Hairong; Deng, Shan; Bai, Qujiang; Zhang, Yu; Zhao, Hong; Liu, Kun; Chu, Yunxia; Ren, Li (Frontiers in Plant Science, 2025)
The accurate quantification of plant organ color remains a major challenge in plant variety identification, particularly when adjacent expression states exhibit subtle visual differences in color. This study addressed this challenge by integrating colorimetric, phenotypic, and genomic analyses of 137 eggplant germplasm resources to characterize their fruit color. The CIELAB color parameters accurately represented fruit coloration and exhibited strong correlations with DNA fingerprinting results, while also aligning with the visual description of color characteristics based on Distinctness, Uniformity, and Stability (DUS) test guidelines. The color transition from harvest maturity to physiological ripeness was effectively captured by shifts in these values. Furthermore, the purple fruits at harvest maturity were subdivided into violet and red subcategories based on their CIELAB parameter distributions, and the yellow, ochre, and brown fruits at physiological ripeness were clearly separated using K-means clustering. Consequently, this study defined precise CIELAB ranges for each color category, offering a robust, multidimensional approach for the objective identification of eggplant varieties and enhancing the reproducibility of color-based DUS evaluations.